2020
DOI: 10.1021/acs.joc.0c02204
|View full text |Cite
|
Sign up to set email alerts
|

Base Promoted Three-Component Annulation of 4-Diazoisochroman-3-imines with Dimethylsulfonium Ylides: Synthesis of Highly Functionalized Isochromeno[4,3-c]pyridazines

Abstract: A novel method has been developed to synthesize a unique class of highly functionalized isochromeno [4,3c]pyridazines. This reaction features an intermolecular functionalization of terminal nitrogen atom of diazo group of 4diazoisochoman-3-imine with two dimethylsulfonium ylide components, followed by a base promoted 6-exo-trig cyclization step. Readily available starting materials, a broad substrate scope, and operationally simple, mild, and catalyst-free reaction conditions are the prominent features of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…On the basis of the experimental results, isolation of intermediate 4 and literature reports, 27,28 a possible reaction mechanism is proposed (Scheme 4). Initially, in the presence of a base pyridinium 2, pyridinium ylide I was generated, which underwent a nucleophilic addition to the electrophilic terminal nitrogen atom of 1 to form a zwitter ionic intermediate II.…”
Section: Papermentioning
confidence: 94%
See 1 more Smart Citation
“…On the basis of the experimental results, isolation of intermediate 4 and literature reports, 27,28 a possible reaction mechanism is proposed (Scheme 4). Initially, in the presence of a base pyridinium 2, pyridinium ylide I was generated, which underwent a nucleophilic addition to the electrophilic terminal nitrogen atom of 1 to form a zwitter ionic intermediate II.…”
Section: Papermentioning
confidence: 94%
“…Recently, intermolecular functionalization of the terminal nitrogen atom of the diazo group of 4-diazoisochoman-3-imine with two dimethylsulfonium ylide components, 27 followed by a base promoted 6- exo-trig cyclization step has been reported for the synthesis of highly functionalized isochromeno[4,3- c ]pyridazines. 28 We have also recently reported the applications of trifluoroacetyl diazoester ( 1 ) for the synthesis of trifluoromethylated heterocyclic compounds. 29 Herein, we report a convenient method for the synthesis of 4-trifluoromethyl pyridazines via annulation of pyridinium ylides ( 2 ) with trifluoroacetyl diazoester ( 1 ) under catalyst-free conditions (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the major development in diazoimine chemistry is associated with electron-deficient 1-sulfonyltriazoles (Scheme A) though some other N1 substituents, most notably fluorinated alkyls, were used . The similar reactivity is observed for sulfonyltriazole-fused indolines , and isochromanes, which exist in diazoimine form exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In contrast to the vast majority of studies focused on the metal carbene precursors, [8] 1,3-dipoles, [9] and C-nucleophiles, [10] the utility of the electrophilic nature for the terminal nitrogen of diazo compounds has scarcely been explored. [11][12][13][14][15] Recently, our group [12] and other groups [13] independently reported the intermolecular nucleophilic addition of one molecule of active methylene compounds to diazo compound as the N-terminal electrophiles. In 2019, Xu and coworkers [14] reported a based-promoted intermolecular nucleophilic addition of two molecules of dimethylsulfonium ylides to α-diazo-β-ketoesters/ketones to produce the corresponding functionalized hydrazones (Scheme 1, a).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Xu and coworkers [14] reported a based-promoted intermolecular nucleophilic addition of two molecules of dimethylsulfonium ylides to α-diazo-β-ketoesters/ketones to produce the corresponding functionalized hydrazones (Scheme 1, a). Very recently, the intermolecular domino cyclization of two dimethylsulfonium ylides with 4-diazoisochoman-3-imines as N-terminal electrophiles was developed for the synthesis of functionalized isochromeno [4,3-c]pyridazines by Wang and co-workers [15] (Scheme 1, b). As part of our research on carbon-carbon and carbon-nitrogen bond-forming reactions, [12,16] herein we reported a 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU)-promoted intermolecular nucleophilic addition of two molecules of nitroalkanes to diazo compounds (Scheme 1, c).…”
Section: Introductionmentioning
confidence: 99%